The Correlation Between Studentsâ€™ Anxiety and Learning Activity towards Their Speaking Ability - Julianingsih, Mira Listia (Journal of Languages and Language Teaching, 2018)
This research was aimed to know the correlationÂ between studentsâ€™ anxiety and learning activity towards their speaking ability at tSMAN 01 Jereweh in academic year 2016/2017. This research was correlation research The sample of the research was all of the second grade students of SMAN 01 Jereweh in academic year 2016-2017 which consists of one class. One class was 28 students. The data was collected by using questionnaireÂ to collected the data of studentsâ€™Â learning activityÂ and Â their anxiety meanwhile Â test to know student speaking ability speaking test was administered.Â TheÂ dataÂ wasÂ analyzedÂ by using person product moment,Â multiple linear regression and multiple correlation. From the data analysis, it was found that the result of correlation score r=0.687. It means the correlation between both of variable Â and Y in moderate correlation because â€œrâ€ score not close enough to +1. And the significant score f=9,523 it mean f=test > f-table of on degree of freedom of 25. Based on the result of the study, in can be concluded there is the the correlationÂ between studentsâ€™anxiety and learning activity towards their speaking abilityÂ at the second grade student of SMAN 01 Jereweh in academic year 2016/2017. It means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected.